Larry gets lost in the twin cities Minneapolis - St. Paul - Mullin, Michael (Sasquatch Books, 2012)
"In Larry the adorable pooch's latest adventure, he goes on vacation with Pete and his family to Minneapolis/St. Paul. As usual, in hot pursuit of a tempting treat, he gets separated from his family and frantically tries to find them again. Along the way he discovers some of the city's most fun and interesting landmarks and cultural attractions, including: Mall of America Hiawatha Line (light rail) Metrodome Mary Tyler Moore statue Skyways Minnehaha Falls Foshay Tower Mill Ruins Park St. Anthony Falls/locks The New Guthrie Theater Walker Art Center sculpture park (Spoonbridge) Lake Harriet (St. Paul) High Bridge Rice Park (Peanuts sculptures) Mickey's Diner Summit Avenue"--